Effect of Azolla microphylla Incorporated Rations on Feed Intake and Nutrient Utilization of Punganur Bulls - Ega, Narendhar Reddy; Busineni, Devasena; Swarna, Venkateswarlu; Gollamoori, Gangaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was carried out to evaluate the effect of incorporation of fresh Azolla microphylla as replacement (0, 10, 20 and 30%)  of crude protein content of concentrate mixture on feed intake, nutrient utilization and cost economics of Punganur bulls. In a 4 x 4  Latin square design, four mature Punganur bulls were fed with four different treatments, i.e., T1 ration (control) comprised of super  napier (Cenchrus purpureus) ad libitum and concentrate mixture with 18% crude protein provided @ 0.5% of the body weight, while  other groups T2, T3 and T4 were fed with ad libitum super napier along with the fresh Azolla microphylla to replace 10, 20 and 30% crude  protein in concentrate mixture, respectively. A significant (p T2 > T1, while digestibility (%) of neutral detergent fibre and cellulose did not differ among the treatments.  The DCP intake (kg/d) was highest (p
Keywords: Azolla microphylla,; Cost economics,; Nutrient digestibility,; Plane of nutrition,; Punganur bulls.